2018
DOI: 10.17582/pujz/2018.33.1.47.53
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Three Days Old Chick Embryos to Permethrin Induced ToxicitiesVulnerability-of-Three-Days-Old-Chick

Abstract: | Agricultural and domestic use of permethrin, a pyrethroid insecticide, has led to intoxication of varying intensities in non target organisms including human. In present study, teratogenicity and embryotoxicity of permethrin was tested in developing chick(Gallus domesticus). Different concentrations of permethrin (0, 5, 10 and 20ppm) were prepared in sterilized distilled water. These doses were injected into eggs on 3 rd day while recovery of embryos was done on 7 th day of incubation. Disrupted embryos with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Therefore, our results may indicate that permethrin exposure slows neuronal development in the cerebellum and other portions of the brain. Permethrin injection into G. domesticus eggs also resulted in microcephaly, as well as microphthalmia, micrognathia, and spina bifida 29,30 . Since we did not observe spina bifida or effects on beak size, and we observed larger eyes in the permethrin‐treated individuals, it is possible that permethrin injection directly into eggs could cause more extreme defects than permethrin exposure through the eggshell.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Therefore, our results may indicate that permethrin exposure slows neuronal development in the cerebellum and other portions of the brain. Permethrin injection into G. domesticus eggs also resulted in microcephaly, as well as microphthalmia, micrognathia, and spina bifida 29,30 . Since we did not observe spina bifida or effects on beak size, and we observed larger eyes in the permethrin‐treated individuals, it is possible that permethrin injection directly into eggs could cause more extreme defects than permethrin exposure through the eggshell.…”
Section: Discussionmentioning
confidence: 70%
“…First, we observed that permethrin treatment reduced overall body size and length of the limbs and toes. This result is supported by studies that showed significantly reduced body weight and crown rump length and increased incidences of small limbs or absence of limbs after permethrin injection into G. domesticus eggs 29,30 . In times of nutrient deficiency during early development, growth of skeletal elements typical slow in favor of shunting resources to vital organs 42 .…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations